A predictive model to determine tensile strength and fracture toughness of 3D printed fiber reinforced concrete loaded in different directions. (June 2022) - Yang, Shutong; Lan, Tian; Sun, Zhongke; Xu, Mingqi; Wang, Mingxin; Feng, Yaodong
Highlights: Anisotropic behavior in crack resistance of 3D printed concrete is clarified. Failure mechanisms of printed concrete loaded in different directions are examined. Physical meaning of microstructure characteristic parameter is clarified. Material heterogeneity and discontinuity are incorporated in the proposed model. Fracture parameters in different loading directions are predicted and compared. Abstract: Concrete 3D printing is getting increased attention in civil engineering. Fibers are generally added to reinforce printed concrete. Crack resistance of 3D printed fiber reinforced concrete in different directions need to be evaluated in a rational manner due to its anisotropic behavior. Therefore, fracture test was performed on printed and mold-cast concrete first in this paper, and failure mechanism were then examined. An analytical model was subsequently proposed based on the analysis of test results to predict the realistic tensile strength f t, fracture toughness K IC and fracture energy G F in different loading directions by incorporating material heterogeneity and discontinuity. The physical meaning of microstructure characteristic parameter reflecting the material heterogeneity was clarified according to the degree of fiber toughness. Closed-form solutions of f t, K IC and G F were obtained related to the maximum fracture load F max . The influence of loading direction on the predicted fracture parameters was analyzed and discussed. Results show that the f t, K IC and G F from specimens loaded perpendicularly to the printing direction were significantly larger than those parallel to the printing direction. Besides, the formers were also higher than the parameters from mold-cast specimens due to the fiber preferential alignment along the printing direction in printed concrete.